Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1525-1594.2000.06432.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Hemodialysis Membranes on Red Blood Cell Susceptibility to Oxidative Stress

Abstract: Oxidative stress is crucial in red blood cell (RBC) damage induced by activated neutrophils in in vitro experiments. The aim of the study was to evaluate whether the bioincompatibility phenomena occurring during hemodialysis (HD) (where neutrophil activation with increased free radical production is well documented) may have detrimental effects on RBC. We evaluated RBC susceptibility to oxidative stress before and after HD in 15 patients using Cuprophan, cellulose triacetate, and polysulfone membrane. RBC were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The interaction of blood with non-biological materials of the extracorporeal circuit during hemodialysis leads to the activation of several non-cellular and cellular systems, including polymorphonuclear leukocytes (PMN) [7, 8]. The activation of PMN may lead to degranulation, with release of several components, namely, cationic proteins and proteases and the production of oxygen metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of blood with non-biological materials of the extracorporeal circuit during hemodialysis leads to the activation of several non-cellular and cellular systems, including polymorphonuclear leukocytes (PMN) [7, 8]. The activation of PMN may lead to degranulation, with release of several components, namely, cationic proteins and proteases and the production of oxygen metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Canaud et al[ 29] suggested that patients on hemodialysis have a pro-oxidative state because of uremia, loss of antioxidant substances during dialysis, hemoincompatibility of the dialysis system and adjuvant therapy. Lucchi et al[ 30] reported increased malonaldehyde content of RBCs with the use of cuprophane membranes when compared with polysulfone and tricellulose acetate membranes. Zima et al[ 31] measured lipid peroxidation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In stage 5 CKD patients, the erythrocytes are metabolically stressed by the unfavourable plasmatic environment, due to metabolite accumulation; by the high rate of haemoglobin autoxidation, due to the increase in haemoglobin turnover, a physiologic compensation mechanism triggered to compensate anaemia (Lucchi, 2000;Stoya, 2002). The erythrocytes will be further stressed during the haemodialysis procedure.…”
Section: Erythrocyte Senescence And/or Damagementioning
confidence: 99%
“…Erythrocytes are physically stressed during the haemodialysis process, and metabolically stressed by the unfavourable plasmatic environment, due to metabolite accumulation, and by the high rate of haemoglobin autoxidation, due to the increase in haemoglobin turnover, a physiologic compensation mechanism triggered in case of anaemia (Lucchi, 2000;Stoya, 2002). The erythrocytes are, therefore, continuously challenged to sustain haemoglobin in its reduced functional form, as well as to maintain the integrity and deformability of the membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation